Impact of dielectric barrier discharge cold plasma on the lipid oxidation, color stability, and protein structures of myoglobin-added washed pork muscle - Wang, Xiaoting; Wang, Jin; Wang, Zhaobin; Yan, Wenjing; Zhuang, Hong; Zhang, Jianhao (Frontiers in Nutrition, 2023)
Cold plasma has been considered a novel nonthermal processing technique and attracted a high attention by the food industry. In this study, the influences of dielectric barrier discharge cold plasma (DBD-CP) on the myoglobin (Mb)-added washed pork muscle (WPM) were evaluated. The electrophoresis pattern, autoxidation, and secondary structure of Mb were analyzed. The results found that DBD-CP caused the decrease of the redness and total sulfhydryl (T-SH) in WPM, while the increase of non-heme, peroxide value (PV), and thiobarbituric acid reactive substances (TBARS), suggested that treatment triggered protein oxidation and heme degradation. Additionally, DBD-CP treatment enhanced the autoxidation of Mb, induced the release of intact heme from the globin, rearranged the charged groups, and promoted Mb aggregation. The transformation of α-helix into the random coil of Mb demonstrated that DBD-CP weakened the tensile strength. Overall, data indicated that DBD-CP promoted autoxidation and changed the secondary structure of Mb, accelerating Mb-mediated lipid oxidation in WPM. Thus, further studies about the optimization of processing conditions by DBD-CP need to be performed.